Manajemen Risiko Proyek Pembangunan Pelabuhan Terminal Kijing Mempawah Pada Masa Pemeliharaan Kontruksi - Ato’urrahman, Muhammad; Ahyudanari, Ervina; Rachmawati, Farida; Machsus, Machsus (GEMA EKONOMI, 2023)
The Maintenance Period is the period of time for the contractor to maintain the results of the work that has been completed. Construction work during the port maintenance period is often carried out when the port is still operating. This condition provides a greater risk for contractors in carrying out repairs. This study uses a case study on the Kijing Terminal Port Development project, West Kalimantan, which is currently under maintenance. The risk of uncertainty issues that have an impact on project performance is the basis for this research to determine risk factors qualitatively by means of literature studies, distributing questionnaires, validating related parties, then approaching using interviews and FGD (Forum Group Discussion). The results of the FGD were then carried out by analyzing the risk response with several methods to determine the effective level of risk and risk response scenarios were carried out. The results of this study obtained the 4 highest risks, namely, high wave weather conditions and natural disasters, improper waste management, budget discrepancies with maintenance cost allocations, and incompatibility of scope of work during the maintenance period with contract documents. The type of risk response can be carried out with a mitigation plan through proactive and reactive actions in accordance with the financial power you have. Contingency costs of IDR 11,656,043,529.255 or 0.393% of the project value.